Phytochemical Composition and In Vitro Antimicrobial Activity of Essential Oils from the Lamiaceae Family against Streptococcus agalactiae and Candida albicans Biofilms - Ramona Iseppi; Roberta Tardugno; Virginia Brighenti; Stefania Benvenuti; Carla Sabia; Federica Pellati; Patrizia Messi (MDPI AG, 2020)
The antimicrobial activity of different essential oils (EOs) from the Lamiaceae family was evaluated on Streptococcus agalactiae, Candida albicans, and lactobacilli. S. agalactiae is the main cause of severe neonatal infections, such as sepsis, meningitis, and pneumonia. C. albicans is a primary causative agent of vulvovaginal candidiasis, a multifactorial infectious disease of the lower female reproductive tract. Lactobacilli represent the dominant bacterial species of the vaginal flora and constitute the natural defense against pathogens. On the basis of the preliminary results, the attention was focused on the EOs from Lavandula x intermedia Emeric ex Loisel. and Mentha arvensis L. By using gas ghromatography (GS) retention data and mass spectra, it was possible to identify more than 90% of the total composition of the EO samples. The minimal inhibitory concentration (MIC) and anti-biofilm activity of the two EOs were determined against all isolated strains, using the EOs by themselves or in combination with each other and with drugs (erythromycin and fluconazole). The results showed a good antimicrobial and anti-biofilm activity of both EOs and a synergistic effect, leading to the best results against all the strains, resulted using the combinations EOs/EOs and antimicrobials/EOs.